Dry Period or Early Lactation—Time of Onset and Associated Risk Factors for Intramammary Infections in Dairy Cows - Nitz, Julia (Pathogens, 2021)
The aim of this study was to define the time-related period of intramammary infections and its relation to risk factors for intramammary infections and clinical mastitis at cow and quarter levels. In total, 269 German Holstein Frisian dairy cows on three farms in Northern and Eastern Germany were included in this study. Quarter milk samples were collected at dry-off, 3 ± 1 days after calving and 17 ± 3 days after calving, for cytomicrobiological examination. Risk factors at quarter- and cow-level associated with intramammary infections and clinical mastitis were recorded during the trial period. Data were analyzed using logistic regression procedures and odds ratios were calculated. Calving for the second time increased the odds of clinical mastitis during the first 100 days of lactation compared to cows calving for the third time or more. A high milk yield after calving was a risk factor for new infections, with environmental pathogens 17 ± 3 days postpartum. A body condition score after calving less than 3.5 was associated with a decreased risk of having an intra-mammary infection (IMI) with non-aureus staphylococci and coryneforms 3 ± 1 days postpartum and consistent body condition between dry-off and early lactation decreased the risk of intramammary infections after calving. The absence of a ring of hyperkeratosis at the teat apex shown at dry-off was associated with a lower risk of intramammary infections with environmental pathogens 17 ± 3 days postpartum. This study shows the important influence of the dry period and early lactation on intramammary infections and clinical mastitis postpartum in dairy cows. Udder quarters may have eliminated pathogens during the dry period in 43.6% of cases in this study. Additionally, new infections occurred during early lactation, so 5.1% more quarters were infected 17 ± 3 days compared to 3 ± 1 days postpartum. New infections can be traced to non-aureus staphylococci and Staphylococcus aureus from dry-off up until 3 ± 1 days postpartum, and to non-aureus staphylococci, Staphylococcus aureus and Streptococcus uberis, after calving. In total, 88.7% of the infected quarters showed new infections with another pathogen species 3 ± 1 days postpartum than at dry-off, and 89.2% of the quarters 17 ± 3 days postpartum than 3 ± 1 days postpartum. In conclusion, the early lactation has just as important an influence on intramammary infections postpartum in dairy cows as the dry period. There is the possibility that udder quarters eliminate pathogens during the early lactation, especially during the dry period. However, there is also the danger that new infections manifest, with a large proportion of new infections occurring after calving. Thus, additional control strategies are of great importance to prevent new infections occurring during early lactation as well as during the dry period to reduce negative effects on milk yield and culling hazards in dairy cows by minimizing the associated risk factors.